2018
DOI: 10.1016/j.biortech.2018.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diclofenac on the production of volatile fatty acids from anaerobic fermentation of waste activated sludge

Abstract: In this study, the impact of diclofenac (DCF), an antiinflammatory drug being extensively used in human health care and veterinary treatment, on the production of volatile fatty acids (VFAs) from anaerobic fermentation of waste activated sludge (WAS) was investigated for the first time. Experimental results showed that when DCF concentration increased from 2.5 to 25 mg/kg total suspended solid (TSS), the maximum production of VFAs increased from 599 to 1113 mg COD/L, but further increase of DCF to 47.5 mg/kg T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…The low sensitivity of hydrogenotrophic methanogens to DCF, compared to other microbial groups is also supported by other works (Table 3) (Symsaris et al 2015;Hu et al 2018).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The low sensitivity of hydrogenotrophic methanogens to DCF, compared to other microbial groups is also supported by other works (Table 3) (Symsaris et al 2015;Hu et al 2018).…”
Section: Resultssupporting
confidence: 81%
“…These results are in good agreement with Fountoulakis et al (Fountoulakis et al 2004), who described 50% of inhibition of the acetoclastic methanogens with 120 mg/L of DCF and a mixture of acetate, casein and yeast extract (Table 3). However, inhibition of acetoclastic methanogenesis of 46% was obtained by Hu et al (Hu et al 2018), for 0.667 mg/L of DCF, with activated sludge from a secondary sedimentation tank of a municipal WWTP as inoculum, and acetate as substrate, revealing a higher susceptibility of that culture to DCF. A lower effect caused by DCF was obtained by Symsaris et al (Symsaris et al 2015), using acetate (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Volatile fatty acids (VFAs) are valuable chemicals produced during the middle stages (acidogenesis and acetogenesis) of anaerobic digestion (AD) 1 . The interest in VFAs relies on their use as building blocks within the renewable-based biorefinery concept 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater treatment plants (WWTPs) are extensively used for biological wastewater treatment to protect natural water bodies from pollution (Chen et al, 2016;Li et al, 2015;Wang et al, 2012a;2012b;. Despite their effective in environmental protection, they are often upset by excessive sludge production (Li et al, 2016;Hu et al, 2018;Wang et al, 2017b;2017c;2018a). For instance, it was reported that ~34 million metric tons of sludge (~20% of solids) were produced in China in 2015 (Feng et al, 2015;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%